Government Spending on Health Care and Education in Croatia : Efficiency and Reform Options - Gunnarsson, Victoria (IMF Working Papers; Working Paper, 2008)
This paper assesses the relative efficiency of government spending on health care and education in Croatia by using the so-called Data Envelopment Analysis. The analysis finds evidence of significant inefficiencies in Croatia's spending on health care and education, related to inadequate cost recovery, weaknesses in the financing mechanisms and institutional arrangements, weak competition in the provision of these services, and weaknesses in targeting public subsidies on health care and education. These inefficiencies suggest that government spending on health and education could be reduced without undue sacrifices in the quality of these services. The paper identifies ways to do that.